Strategy for Isolated Iliac Artery Aneurysms - Hiromatsu, Shinichi; Hosokawa, Yukio; Egawa, Noriko; Yokokura, Hiroko; Akaiwa, Keiichi; Aoyagi, Shigeaki (Asian cardiovascular & thoracic annals, 2007)
We retrospectively reviewed 41 patients with isolated iliac artery aneurysms presenting over a 21-year period. The mean age was 72 years. Mean aneurysmal diameter was 6.0 cm (range, 3.2–13 cm). The aneurysms were located in the common iliac artery in 31 patients, internal iliac artery in 7, and both arteries in 3. Rupture occurred in 20 patients (49%). The frequency of rupture of isolated iliac artery aneurysms was significantly higher than that of abdominal aortic aneurysms (8%) during the same period. The 30-day mortality was 9.8%; death in all 4 patients was due to rupture of the aneurysm. The surgical procedure was aneurysmectomy and replacement with a bifurcated prosthetic graft in 24 patients (59%), closure of the common iliac artery with a femorofemoral crossover in 7, minilaparotomy in 3, thromboexclusion in 6, and endoluminal stent-graft repair in one. In contrast to abdominal aortic aneurysms, isolated iliac artery aneurysms can be treated by various methods other than replacement with a bifurcated prosthetic graft. When selecting a strategy for such aneurysms, it is important to choose an approach appropriate to the location and risk, because of the frequency of rupture.